Gel-state electrolyte and preparation method thereof, and zinc-bromine microbattery and preparation method thereof

By using gel electrolytes in zinc-brominated microbatteries, the problems of low efficiency, short cycle life and high capacity loss in zinc-brominated microbatteries under low temperature conditions are solved, and efficient and stable battery performance is achieved, which is suitable for a wide range of temperatures.

CN119542576AActive Publication Date: 2025-02-28SICHUAN UNIV

Patent Information

Application Number
CN202411963337.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-02-28
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Zinc-brominated microbatteries have low efficiency, short cycle life and high capacity loss under low temperature conditions.

Method used

A gel electrolyte was prepared by immersing the dry gel in the electrolyte solution, and the gel electrolyte containing bromide ions and zinc ions was prepared. The zinc ions concentration was 5 to 12.5 mol/L and the bromide ions concentration was 10 to 25 mol/L. This method does not require additional complexing agents and antifreeze agents, and is directly used in the preparation of zinc-brominated microcells.

Benefits of technology

It significantly improves the Coulomb efficiency and cycle life of zinc-brominated microbatteries, and can maintain high capacity and stability under low temperature conditions. It is suitable for power supply equipment for flexible or micro electronic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542576A_ABST
    Figure CN119542576A_ABST
Patent Text Reader

Abstract

The invention provides a gel-state electrolyte and a preparation method thereof, and a zinc-bromine microbattery and a preparation method thereof, and belongs to the technical field of aqueous static zinc-bromine batteries. The xerogel is soaked in an electrolyte to obtain a gel-state electrolyte, ions in the electrolyte comprise bromide ions and zinc ions with electrochemical activity, and the concentration of the zinc ions is 5-12.5 mol / L. Reassembling the zinc-bromine microbattery through the gel-state electrolyte; a complexing agent and an anti-freezing agent do not need to be additionally added into the gel-state electrolyte, the preparation method is simple, the zinc-bromine microbattery can be used as energy supply equipment of flexible or microelectronic devices, the use scene and the application prospect of the zinc-bromine battery are remarkably widened, and stable energy supply can also be achieved under the variable-temperature condition. The zinc-bromine microbattery can be cycled for more than 5000 times at normal temperature, the specific capacity is 184 mu Ah.cm <-2 >, the zinc-bromine microbattery can also be cycled for more than 500 times at the temperature of-60 DEG C, and the capacity retention ratio is 98%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of aqueous static zinc-bromine batteries, and in particular to a gel electrolyte and a preparation method thereof, and a zinc-bromine microbattery and a preparation method thereof. Background Art

[0002] With the emergence of various miniaturized electronic devices such as micro-supercapacitors, micro-robots, and wearable sensors, the application potential of micro-energy storage devices is growing. Therefore, high-performance, easy-to-manufacture micro-batteries have been widely studied. Zinc-ion batteries have become a promising energy storage system in large-scale energy storage due to their high theoretical capacity, abundant reserves, safety and high efficiency. Among them, zinc-bromine micro-batteries have high energy density, fast reaction kinetics, and high output voltage. However, the capacity loss of zinc-bromine micro-batteries under low temperature conditions is an urgent problem to be solved. During the charge and discharge process of zinc-bromine batteries, the cathode charging product Br2 reacts with Br in the electrolyte. - The formation of polybrominated n - , n≥3). The shuttling effect of soluble polybromides directly leads to reduced coulombic efficiency and shortened cycle life. The current mainstream solution is to limit polybromides by complexing agents to avoid cross-diffusion of active substances. This method will greatly increase the internal resistance and cost, so it is not suitable for manufacturing batteries working at low temperatures. On the other hand, the studies reported so far mainly adopt the strategy of adding organic antifreeze to reduce the high freezing point of aqueous electrolytes. However, the introduced polar organic antifreeze will cause the polybromides to dissolve. This will cause cross-diffusion of active substances, thereby reducing the coulombic efficiency and cycle life of the battery. In addition, the addition of antifreeze will reduce the utilization rate of the electrolyte and affect the kinetics of the electrochemical reaction. These methods cannot simultaneously solve the problems encountered by zinc-bromine batteries working at low temperatures, so it is difficult to meet the practical application needs of zinc-bromine batteries. Summary of the invention

[0003] The purpose of the present invention is to provide a gel electrolyte and a preparation method thereof and a zinc-bromine microbattery and a preparation method thereof, so as to solve the problems of low coulombic efficiency, short cycle life and high capacity loss under low temperature conditions of zinc-bromine microbatteries in the prior art.

[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing a gel electrolyte, comprising the following steps: immersing a dry gel in an electrolyte to obtain a gel electrolyte;

[0006] The ions in the electrolyte include bromide ions and zinc ions, and the concentration of the zinc ions is 5 to 12.5 mol / L.

[0007] Preferably, the concentration of bromide ions is 10 to 25 mol / L.

[0008] Preferably, the xerogel is polyacrylamide xerogel or sodium carboxymethylcellulose xerogel.

[0009] Preferably, the impregnation is performed until saturation impregnation is achieved.

[0010] Preferably, the polyacrylamide xerogel is prepared by polymerizing acrylamide monomer, ammonium persulfate and N,N'-methylenebisacrylamide in water, and then standing and drying to obtain the polyacrylamide xerogel.

[0011] Preferably, the preparation method of the sodium carboxymethyl cellulose xerogel is: mixing sodium carboxymethyl cellulose and water at 40-70° C. for 0.5-3 h, then standing and drying to obtain the sodium carboxymethyl cellulose xerogel.

[0012] The present invention also provides a gel electrolyte prepared by the above-mentioned method for preparing the gel electrolyte.

[0013] The present invention also provides a zinc-bromine microbattery, which comprises a flexible substrate, a positive electrode, a negative electrode and the gel electrolyte described above.

[0014] The present invention also provides a method for preparing the zinc-bromine microbattery, comprising the following steps: attaching a positive electrode and a negative electrode to a flexible substrate respectively, then covering the positive electrode and the negative electrode with a gel electrolyte, and finally packaging to obtain a zinc-bromine microbattery.

[0015] Preferably, the area of ​​the positive electrode and the negative electrode are independently 0.1 to 5 cm 2 ; The thickness of the gel electrolyte is 2 to 5 mm.

[0016] Beneficial effects of the present invention:

[0017] (1) The present invention uses the influence of zinc ions and bromide ions on hydrogen bond structure in a strong electric field and the unique solvation reconstruction effect in aqueous electrolytes to destroy the hydrogen bonds between water molecules in aqueous electrolytes. The hydrogen bonds and ion interactions are balanced by concentration adjustment, and the solidification point of the prepared gel electrolyte is extremely low, and the prepared zinc-bromine microbattery has a high ionic conductivity.

[0018] (2) The present invention achieves a complexing effect on polybromides by regulating the concentration of cations in a strong electric field, thereby inhibiting the shuttling effect of polybromides, thereby inhibiting the diffusion of positive electrode charging products, and effectively improving the stability of the zinc-bromine microbattery.

[0019] (3) No additional chelating agent or antifreeze agent is required in the gel electrolyte, and the preparation method is simple, which greatly improves the electrolyte utilization, safety, and practicality of zinc-bromine microbatteries.

[0020] (4) The zinc-bromine microbattery of the present invention can be used as a power supply device for flexible or microelectronic devices, which significantly broadens the operating temperature range of the zinc-bromine microbattery and can also provide energy stably under variable temperature conditions.

[0021] (5) The ionic conductivity of the gel electrolyte of the present invention at room temperature can be as high as 62.5 mS·cm -1 , the ionic conductivity can reach up to 10.1mS·cm at -20℃ -1 , the ionic conductivity can reach up to 4.1mS·cm at -40℃ -1 , the ionic conductivity can reach up to 0.8mS·cm at -60℃ -1 .

[0022] (6) The zinc-bromine microbattery of the present invention can be cycled more than 5000 times at room temperature, with a specific capacity of 184 μAh·cm -2 , it can be cycled more than 500 times at a temperature of -60°C, and the capacity retention rate is 98%. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is a schematic diagram of the structure of the zinc-bromine microbattery of the present invention;

[0024] Figure 2 This is a charge and discharge cycle performance diagram of the zinc-bromine microbattery of Example 1 under normal temperature conditions;

[0025] Figure 3 This is a rate performance diagram of the zinc-bromine microbattery of Example 1;

[0026] Figure 4 This is a temperature performance diagram of the zinc-bromine microbattery of Example 1;

[0027] Figure 5 This is a charge and discharge cycle performance diagram of the zinc-bromine microbattery of Example 1 at a temperature of -60°C;

[0028] Figure 6 This is a photo of the zinc-bromine microbattery of the present invention powering an electronic watch in a bent state;

[0029] Figure 7 This is a charge and discharge cycle performance diagram of the zinc-bromine microbattery of Example 2 under normal temperature conditions;

[0030] Figure 8 This is a temperature performance diagram of the zinc-bromine microbattery of Example 2;

[0031] Fig. 9This is a charge and discharge cycle performance diagram of the zinc-bromine microbattery of Example 3 under normal temperature conditions;

[0032] Fig.10 This is a temperature performance diagram of the zinc-bromine microbattery of Example 3;

[0033] Fig.11 This is a temperature performance diagram of the zinc-bromine microbattery of Comparative Example 1;

[0034] Fig.12 This is the temperature variation performance diagram of the zinc-bromine microbattery of comparative example 2.

[0035] Fig.13 This is the temperature variation performance diagram of the zinc-bromine microbattery of comparative example 3. DETAILED DESCRIPTION

[0036] The present invention provides a method for preparing a gel electrolyte, comprising the following steps: immersing a dry gel in an electrolyte to obtain a gel electrolyte;

[0037] The ions in the electrolyte include bromide ions and zinc ions, wherein the concentration of the zinc ions is 5 to 12.5 mol / L.

[0038] In the present invention, the concentration of the zinc ion is preferably 7.5 to 12.5 mol / L

[0039] In the present invention, the concentration of bromide ions is 10 to 25 mol / L, preferably 15 to 25 mol / L.

[0040] In the present invention, the xerogel is polyacrylamide xerogel or sodium carboxymethylcellulose xerogel.

[0041] In the present invention, the impregnation is performed until saturation impregnation is achieved.

[0042] In the present invention, the preparation method of the polyacrylamide xerogel is as follows: acrylamide monomer, ammonium persulfate and N,N'-methylenebisacrylamide are added to water, mixed at 40-70°C for 0.2-1h, kept at 40-70°C for 8-16h, and then allowed to stand and dried to obtain the polyacrylamide xerogel. The polymerization process is preferably mixed at 50-65°C for 0.3-0.7h, kept at 50-65°C for 10-14h, and more preferably mixed at 58-62°C for 0.5h, and kept at 58-62°C for 11-12.5h.

[0043] In the present invention, the mass ratio of the acrylamide monomer, ammonium persulfate, N,N'-methylenebisacrylamide and water is 1500-3000:6-15:0.5-2.5:10000-20000.

[0044] In the present invention, the preparation method of the sodium carboxymethyl cellulose xerogel is as follows: sodium carboxymethyl cellulose powder and water are mixed at 40-70° C. for 0.5-3 h, preferably at 60° C. for 1.5 h, and then allowed to stand and dried to obtain the sodium carboxymethyl cellulose xerogel.

[0045] In the present invention, the mass ratio of the sodium carboxymethyl cellulose to water is 1:200 to 1:400.

[0046] In the present invention, the electrolyte is impregnated with the dry gel, and the gel is used as a carrier of the electrolyte to achieve the bending effect of the flexible battery.

[0047] The present invention also provides a gel electrolyte prepared by the above-mentioned method for preparing the gel electrolyte.

[0048] The present invention also provides a zinc-bromine microbattery, which comprises a flexible substrate, a positive electrode, a negative electrode and the gel electrolyte described above.

[0049] In the present invention, the material of the flexible substrate includes polyvinyl alcohol, polyethylene terephthalate, polyimide or polyethylene naphthalate, preferably polyethylene terephthalate.

[0050] In the present invention, the material of the positive electrode includes titanium foil, stainless steel foil, carbon nanotube paper or carbon cloth, preferably carbon nanotube paper.

[0051] In the present invention, the material of the negative electrode includes zinc foil, titanium foil, stainless steel foil, carbon nanotube paper or carbon cloth, preferably carbon nanotube paper.

[0052] The present invention also provides a method for preparing the zinc-bromine microbattery, comprising the following steps: attaching a positive electrode and a negative electrode to a flexible substrate respectively, then covering the positive electrode and the negative electrode with a gel electrolyte, and finally packaging to obtain a zinc-bromine microbattery.

[0053] In the present invention, the areas of the positive electrode and the negative electrode are independently 0.1 to 5 cm 2 , preferably 0.1 to 3 cm 2 , more preferably 0.2 to 2 cm 2 ; The thickness of the gel electrolyte is 2 to 5 mm, preferably 3 to 4 mm.

[0054] In the present invention, the area of ​​the gel electrolyte is larger than the sum of the areas of the positive electrode and the negative electrode.

[0055] In the present invention, the packaging is preferably performed using polyimide tape.

[0056] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0057] Example 1

[0058] 2.9 g of acrylamide monomer, 14.3 mg of ammonium persulfate, 1.8 mg of N,N'-methylenebisacrylamide and 20 mL of deionized water were mixed, stirred at 60°C for 0.5 h, then kept warm for 12 h to obtain polyacrylamide hydrogel, and finally the polyacrylamide hydrogel was dried at 60°C for 12 h to obtain polyacrylamide xerogel.

[0059] Zinc bromide was dissolved in deionized water to obtain an electrolyte (wherein the concentration of zinc ions was 7.5 mol / L and the concentration of bromide ions was 15 mol / L), and the polyacrylamide dry gel was immersed in the electrolyte. After immersion for 3 days until saturation was reached, the dry gel was taken out to obtain a gel electrolyte.

[0060] Place the carbon nanotube paper in a laser printer and cut it into the required shape to ensure that the positive and negative electrodes have the same area. The electrode area is 0.2 cm 2 The positive electrode and the negative electrode were separately attached to a polyethylene terephthalate flexible substrate, and then a gel electrolyte (3 mm thick) was covered on the positive and negative electrodes to ensure that the area of ​​the gel electrolyte was larger than the sum of the areas of the positive and negative electrodes. Finally, they were packaged with polyimide tape to obtain a zinc-bromine microbattery.

[0061] from Figure 2 It can be seen that the zinc-bromine microbattery of this embodiment can be cycled more than 5000 times at room temperature, with a capacity of 184 μAh·cm -2 .from Figure 3 It can be seen that the zinc-bromine microbattery in this embodiment has a capacity of 1 to 20 mAh·cm -2 The capacity retention rate is 94%. Figure 4 It can be seen that the zinc-bromine microbattery of this embodiment has no capacity loss at a temperature of -60°C. Figure 5 It can be seen that the zinc-bromine microbattery of this embodiment can be cycled for more than 500 times at a temperature of -60°C, and the capacity retention rate is 98%.

[0062] Example 2

[0063] The difference from Example 1 is that the concentration of zinc ions in the electrolyte is 10 mol / L, the concentration of bromide ions is 20 mol / L, and other conditions are the same.

[0064] from Figure 7 It can be seen that the zinc-bromine microbattery of this embodiment can be cycled more than 3000 times at room temperature, and the capacity reaches 183.1 μAh·cm -2 .from Figure 8It can be seen that the zinc-bromine microbattery of this embodiment has only a small capacity loss at a temperature of -60°C.

[0065] Example 3

[0066] The difference from Example 1 is that the concentration of zinc ions in the electrolyte is 12.5 mol / L, the concentration of bromide ions is 25 mol / L, and other conditions are the same.

[0067] from Fig. 9 It can be seen that the zinc-bromine microbattery of this embodiment can be cycled more than 3000 times at room temperature, and the capacity reaches 182.6 μAh·cm -2 .from Fig.10 It can be seen that the zinc-bromine microbattery of this embodiment has only a small capacity loss at a temperature of -60°C.

[0068] Comparative Example 1

[0069] The difference from Example 1 is that the concentration of zinc ions in the electrolyte is 15 mol / L, the concentration of bromide ions is 30 mol / L, and other conditions are the same.

[0070] from Fig.11 It can be seen that the zinc-bromine microbattery prepared in Comparative Example 1 has poor antifreeze performance, and its capacity decreases when the temperature drops to -60°C, with a capacity retention rate of only 69%.

[0071] Comparative Example 2

[0072] The difference from Example 1 is that the concentration of zinc ions in the electrolyte is 2.5 mol / L, the concentration of bromide ions is 5 mol / L, and other conditions are the same.

[0073] from Fig.12 It can be seen that the zinc-bromine microbattery prepared in Comparative Example 2 has poor antifreeze performance, and its capacity is greatly reduced when the temperature drops to -60°C. The zinc-bromine microbattery fails below -50°C.

[0074] Comparative Example 3

[0075] The difference from Example 1 is that the zinc ion concentration in the electrolyte is 10 mol / L, the chloride ion concentration is 15 mol / L, the bromide ion concentration is 5 mol / L, and other conditions are the same.

[0076] from Fig.13 It can be seen that the zinc-bromine microbattery prepared in Comparative Example 3 has poor antifreeze performance, a capacity retention rate of 82%, and as the number of cycles increases, the discharge capacity also decreases.

[0077] Figure 6The photo of the zinc-bromine microbattery powering an electronic watch in a bent state shows that it is flexible and can be used in flexible devices.

[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a gel electrolyte, characterized in that: The method comprises the following steps: immersing the dry gel in an electrolyte to obtain a gel electrolyte; The ions in the electrolyte include bromide ions and zinc ions, and the concentration of the zinc ions is 5 to 12.5 mol / L.

2. The method for preparing a gel electrolyte according to claim 1, characterized in that: The concentration of the bromide ions is 10 to 25 mol / L.

3. The method for preparing a gel electrolyte according to claim 2, characterized in that: The xerogel is polyacrylamide xerogel or sodium carboxymethylcellulose xerogel.

4. The method for preparing a gel electrolyte according to any one of claims 1 to 3, characterized in that: The impregnation is performed until saturation impregnation is achieved.

5. The method for preparing a gel electrolyte according to claim 4, characterized in that: The preparation method of the polyacrylamide xerogel comprises the following steps: polymerizing acrylamide monomer, ammonium persulfate and N,N'-methylenebisacrylamide in water, and then standing and drying to obtain the polyacrylamide xerogel.

6. The method for preparing a gel electrolyte according to claim 4, characterized in that: The preparation method of the sodium carboxymethyl cellulose dry gel is as follows: sodium carboxymethyl cellulose and water are mixed, and then allowed to stand and dried to obtain the sodium carboxymethyl cellulose dry gel.

7. A gel electrolyte obtained by the method for preparing a gel electrolyte according to any one of claims 1 to 6.

8. A zinc-bromine microbattery, characterized in that: The zinc-bromine microbattery comprises a flexible substrate, a positive electrode, a negative electrode and the gel electrolyte according to claim 7.

9. The method for preparing the zinc-bromine microbattery according to claim 8, characterized in that: The method comprises the following steps: attaching a positive electrode and a negative electrode to a flexible substrate respectively, then covering the positive electrode and the negative electrode with a gel electrolyte, and finally packaging to obtain a zinc-bromine microbattery.

10. The method for preparing the zinc-bromine microbattery according to claim 9, characterized in that: The areas of the positive electrode and the negative electrode are independently 0.1 to 5 cm 2 ; The thickness of the gel electrolyte is 2 to 5 mm.

Citation Information

Patent Citations

  • Preparation and application of gel electrolyte for anti-freezing zinc-based battery

    CN113851739A

  • Anti-zinc dendrite solid-state zinc-based battery electrolyte and preparation method thereof

    CN114122534A

  • Aqueous zinc-bromine battery

    CN116315160A

  • Colloidal electrolyte of colloidal zinc-bromine battery and preparation method of colloidal electrolyte

    CN116435617A

  • Secondary battery

    JP1994196199A

Cited By

  • Preparation method of electrolyte for semi-solid zinc-bromine battery, semi-solid zinc-bromine battery and preparation method of semi-solid zinc-bromine battery

    CN121839782A